Exploring Inequalities in the Use, Quality, and Outcome of the Diabetes Management Program of Indonesian National Health Insurance (Mary Ann Liebert, 2023)
Introduction: Access to diabetes management programs is crucial to control the increasing contribution of diabetes to the global burden of disease. However, evidence regarding whether such services are equally accessible for all population groups is still lacking, particularly in the context of low-middle-income countries and under the National Health Insurance (NHI). This study aimed to assess the extent of socioeconomic and geographical inequalities in the use, quality, and outcome of a diabetes management program for beneficiaries of Indonesian NHI. Methods: A total of 628 participants in the NHI diabetes management program in Banyumas District, Indonesia, were included in 2021 in this cross-sectional study. The main variables measured were regular visits to primary care facilities, standard medication, and glycemic control. The rate difference and rate ratio of age-sex standardized prevalence rates, as well as multiple logistic regressions, were used to measure the extent of inequalities. Results: Around 70% of participants regularly visited primary care facilities and received standard medication, but only 35% had good glycemic control. Highly educated participants were more likely to have regular visits compared to low-educated participants (odds ratio [OR] 1.92; 95% confidence interval [95% CI]: 1.04?3.56). Based on employment and type of NHI beneficiaries, a small extent and even reverse inequalities were found although these findings were insignificant statistically. Urban residents were also more likely to have regular visits (OR 6.61; 95% CI: 2.90?15.08), receive standard medication (OR 9.73; 95% CI: 3.66?25.90), and have good glycemic control (OR 3.85; 95% CI: 1.68?8.83) compared to rural residents. Conclusions: Evidence on the extent of socioeconomic inequalities is inconclusive but substantial geographical inequalities in the use, quality, and outcome of diabetes management programs exist among Indonesian NHI beneficiaries. Future implementation policies of the program should consider particularly the geographical characteristics of participants to avoid and reduce inequalities and, hence, the disease burden of diabetes.